The Serological Surveillance of Hepatitis E virus among Hunters and Foresters in Eastern Poland - Marcin Weiner; Małgorzata Tokarska-Rodak; Dorota Plewik; Anna Pańczuk; Adam Szepeluk; Monika Krajewska (Polish Journal of Microbiology, 2017)
The aim of the study was the analysis of the occurrence of specific antibodies against HEV among hunters and foresters who are at risk to be exposed. The study group consisted of 210 hunters (23–80 years old) and 60 foresters (22–64 years old). Anti-HEV IgG were present in 3.81% of the samples of the hunters and in 5% of the samples of the foresters. The statistical analysis shows no significant differences inthe results anti-HEV IgG between the groups of hunters and foresters (p = 0.5278). Significantly higher anti-HEV IgG titers were foundin the older age group (> 55 years old).